Multiscale Multiphysics Coupling on a Finite Element Platform - Cerroni, Daniele <1988> (Alma Mater Studiorum - Università di Bologna, 2016)
In recent years numerical simulations are becoming fundamental for the design of many engineering components. For this reason many multiphysical and multiscale problems are investigated by coupling different existent software created specifically for solving each single problem. However, because of the intrinsic differences among these codes, such coupling is very challenging. In this thesis we develop a computational platform that can be used to integrate different computing tools into the common framework of the SALOME platform. Inside this platform various codes are coupled through numerical libraries with the purpose of exchanging data and melting intrinsic differences. After a description of the generic code integration procedure into the numerical platform, we introduce three classes of problems where different codes have been coupled and complex computational problems are studied. In the irst problem class, the computational platform is used to study a nuclear reactor system. We study the dynamics of a multiscale primary loop of a liquid metal reactor by coupling a mono-dimensional system code with the high resolution three-dimensional full scale core components models. Also we investigate a thermal-hydraulic-neutron multiphysics problem. The heat energy production in the reactor core, obtained by solving the neutron code DRAGON-DONJON, is coupled with the solution of the thermal-hydraulics conservative equations implemented in a in-house code. In the second problem class, we consider multiscale multiphysics Fluid Structure Interaction problems implemented in different modules of the FEMUs code. The mechanics of a three-dimensional particular component of the cardiovascular system is coupled with a mono-dimensional model that takes into account the remaining parts of a simplified circulatory system. Finally, in the last class of problems, Multiphase Fluid tructure Interaction problems are investigated by coupling the solution of a multiphase fluid interface advection VOF module with a FSI solver.